Rancang Bangun Sistem Informasi Biaya Perjalanan Dinas - Nurfarida Nurfarida; Hilda Amalia; Yunita Yunita (JURNAL TEKNIK KOMPUTER, 2020)
Abstract- Business travel is a routine activity carried out by almost all government agencies in Indonesia. Business travel requires special budgeting costs and at the end of the activity a report on the use of costs or an approved budget is required. Problems encountered in the official travel costs system take quite a long time to produce an effective and efficient travel expense report. Difficulties in monitoring business trips conducted both in terms of cost and time. Searching for travel cost data also takes a long time, making it difficult for auditing of official travel costs. For this reason it is important for all agencies or companies to create information systems that are known to be able to produce reports that are fast, accurate and accurate and able to carry out monitoring of official travel activities undertaken. The results of this study are an information system for official travel financing.                                                                                Keywords: official travel, cost, information system